The Effect of Sleep Hygiene Therapy on Sleep Quality in Premenopausal Women in the Sememi Health Center Area - Yukendri, Nurnikensari; Isfentiani, Dina; Aini, Elfira Nurul; Ernawati, Masfuah (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
During premenopause, certain changes occur due to a decrease in estrogen levels which can cause mild to severe disorders, as well as physical and psychological changes. These changes, which often occur during premenopause, cause complaints, one of which is insomnia or difficulty sleeping, which makes the incidence of poor sleep quality in adult women / premenopausal mothers equal to 57.8%. To improve sleep quality, it is necessary to carry out sleep hygiene therapy. Therefore, the effect of sleep hygiene therapy on sleep quality in premenopausal women in the Sememi Surabaya Community Health Center area will be studied. This research is a Quasy Experiment research with One Group Pretest-Posttest Design. The population of this study was 90 premenopausal mothers. The sample was taken by Purposive Sampling of 48 respondents. The independent variable is sleep hygiene therapy, while the dependent variable is premenopausal women. Data collection uses questionnaires. To analyze the presence of an influence, the Wilcoxon Signed Rank Test was used with p <0,05. The results of the study showed that there was an increase in sleep quality in premenopausal mothers before and after sleep hygiene therapy. After conducting the test, the results showed that there was an effect of sleep hygiene therapy on sleep quality in premenopausal women in the Sememi Surabaya Community Health Center area with a p value of 0.004 < α 0.05. Based on the description above, it can be concluded that there is an influence of sleep hygiene therapy on sleep quality in premenopausal women in the Sememi Surabaya Community Health Center area. So it is recommended that premenopausal mothers make the best use of sleep hygiene therapy, because maintaining good sleep quality is good for premenopausal mothers.